Unraveling the neuroprotective mechanisms of elephant black garlic extract against beta amyloid peptide-induced neurotoxicity - Gavilan, Javiera; Panes-Fernández, Jessica; Araya, Aníbal; Pérez-Manríquez, Claudia; Becerra, José; Varas, Patricio; Moraga-Cid, Gustavo; Yévenes, Gonzalo E.; Fuentealba, Jorge (Frontiers in Nutrition, 2026)
Chilean Elephant Black Garlic (Allium ampeloprasum) is a distinctive variety whose biological activity remains largely unexplored. Unlike conventional black garlic derived from Allium sativum, this preparation exhibits a markedly different chemical profile enriched in sulfur-containing metabolites such as 3H-1,2-dithiol-3-thione (D3T) and 4-methyl-1,2,3-trithiolane (TTL). These compounds are rarely detected in traditional black garlic extracts and may underlie the specific protective effects observed in this study. Consequently, the biological actions described here cannot be generalized to other black garlic preparations. We provide the first evidence that Chilean Elephant Black Garlic (BG) confers neuroprotection against the toxicity of soluble oligomers of amyloid-beta (SO-Aβ), a central pathogenic element of Alzheimer’s disease (AD) known to trigger synaptic dysfunction and mitochondrial impairment. In mouse hippocampal slices, BG prevented SO-Aβ-induced reductions in cell viability. Complementary experiments in cultured hippocampal neurons showed that BG preserved spontaneous calcium signaling and prevented SO-Aβ-mediated alterations in neuronal arborization. At the molecular level, BG restored the expression of synaptic proteins (SV2 and PSD-95) and maintained BDNF levels. Beyond synaptic protection, BG also preserved mitochondrial function under SO-Aβ challenge by maintaining mitochondrial membrane potential, intracellular ATP levels, and Mitofusin-1 expression. Altogether, these findings identify Chilean Elephant Black Garlic, as functional food, that represent an important source of bioactive compounds with properties capable of counteracting key neurotoxic mechanisms implicated in AD.